ANALISIS EFISIENSI DAN PENDAPATAN USAHA PEMBIBITAN KARET PADA PTPN III KEBUN RAMBUTAN TEBING TINGGI, SUMATERA UTARA - Nurung, M. (Jurnal AGRISEP, 2009)
The objective of this research was to know the number of income and level of efficiency in rubbers seeding business at PTPN III Kebun Rambutan. This research was done in five rubber seeding blocks in PTPN III Kebun Rambutan. PTPN III Kebun Rambutan was chosen as the place of the research because this company was the only one company that sold its rubber seeds to local consumers. The results of this research was shown that the average of real R/C Ratio was 1,81 and the unreal was 1,85 the meaning was efficient . The average of PTPN III Kebun Rambutan real income was Rp 1.166.509.090,93/Ut/5 months and the unreal income was Rp 1.221.160.5